Net Profit Margin as Driver of Firm Value: A Study of The Pharmaceutical Sector Listed on IDX - Rosita, Yeti (Manunggal Halim Jaya, 2024)
This study aims to analyse the effect of Net Profit Margin (NPM) on firm value, as measured using Price to Book Value (PBV) in the pharmaceutical sector in Indonesia. Profitability is often considered a major factor in determining firm value, but the relationship between NPM and PBV is still debated in various previous studies. This study uses panel data from 7 pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. The analysis method used is panel data regression with a fixed effects approach (FEM) to capture differences in characteristics between companies. The results showed that Net Profit Margin (NPM) has no significant effect on firm value (PBV) with a coefficient value of -0.0061 and a p-value of 0.7531. Although the overall model is significant (Prob F-statistic = 0.0000), the NPM variable does not play a major role in explaining variations in firm value in the pharmaceutical sector. This indicates that other factors, such as capital structure, revenue growth, and market conditions, may have more influence on firm value than profitability alone. This study contributes to academics and financial practitioners in understanding the factors that influence firm value in the pharmaceutical industry. The implication of these findings is that financial managers and investors need to consider other variables besides profitability in assessing the prospects and valuation of pharmaceutical companies.